Attack of the Killer Microseconds. - BARROSO, BY LUIZ; MARTY, MIKE; PATTERSON, DAVID; RANGANATHAN, PARTHASARATHY (Communications of the ACM, 2017)
The article discusses the influence of low-latency I/O devices on efforts to mitigate microsecond-scale event latencies within computer systems. Topics include processor designers' development of techniques such as prefetching, out-of-order execution, and branch prediction to facilitate a deep memory hierarchy that works at nanosecond scale by providing a simple synchronous programming interface to memory systems, and computer scientists' creation of software-based techniques, such as operating system context switching, to handle millisecond-scale events.